2020
DOI: 10.5430/ijfr.v11n6p188
|View full text |Cite
|
Sign up to set email alerts
|

Co-integration and Causal Relationships: The Case of the Jordanian and Developed Stock Markets

Abstract: The main purpose of this study is to investigate co-integration and causal relationships among the Jordanian, the US, and the UK stock markets. The vector error correction model is applied using yearly stock market indices series for the period, 1978 – 2018. The results reveal the existence of co-integration and causal relationships among stock markets indices. These results indicate the scope for diversification profits, where the Jordanian investors secure higher levels of mean returns on the diversified por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Our findings show that the U.S. stock market index (S&P 500) is crucial in the ASEI prediction model. is result is consistent with [19], who found integration and causal relationship between ASEI and U.S. stock markets. Finally, financial markets tend to behave similarly, especially during the financial crisis, health crisis, and political instability such as the Arab spring revolutions.…”
Section: Artificial Neural Networksupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings show that the U.S. stock market index (S&P 500) is crucial in the ASEI prediction model. is result is consistent with [19], who found integration and causal relationship between ASEI and U.S. stock markets. Finally, financial markets tend to behave similarly, especially during the financial crisis, health crisis, and political instability such as the Arab spring revolutions.…”
Section: Artificial Neural Networksupporting
confidence: 91%
“…Few researchers have tried to estimate the relationship between international stock market indices and Amman Stock Exchange Index (ASEI) and predict one of the ASE subindices. Reference [19] showed that the co-integration and causal relationship exists among ASEI, U.S. stock markets, and the U.K. market.…”
Section: Prediction Of Amman Stock Exchange Index (Asei) and Ase Subs...mentioning
confidence: 99%
See 1 more Smart Citation